# User:Cornince/no2

{\displaystyle {\begin{aligned}&\sum _{i=0}^{n}(-1)^{i}{n \choose i}z(n-i+(m+1))-\sum _{i=0}^{n}(-1)^{i}{n \choose i}z(n-i+m)\\&=z(n+1+m)-(-1)^{n}z(m)+\sum _{i=1}^{n}(-1)^{i}{n \choose i}z(n-i+m+1)-\sum _{i=0}^{n-1}(-1)^{i}{n \choose i}z(n-i+m)\\&=z(n+1+m)+(-1)(-1)^{n}z(m)+\sum _{i=1}^{n}(-1)^{i}{n \choose i}z(n-i+m+1)+(-1)\sum _{i=1}^{n}(-1)^{(i-1)}{n \choose (i-1)}z(n-(i-1)+m)\\&=z((n+1)+m)+(-1)^{(n+1)}z(m)+\sum _{i=1}^{n}(-1)^{i}{n \choose i}z(n-i+m+1)+\sum _{i=1}^{n}(-1)^{i}{n \choose i-1}z(n-i+m+1)\\&=z((n+1)+m)+(-1)^{(n+1)}z(m)+\sum _{i=1}^{n}(-1)^{i}\left[{n \choose i}+{n \choose i-1}\right]z(n-i+m+1)\\&=z((n+1)+m)+(-1)^{(n+1)}z(m)+\sum _{i=1}^{n}(-1)^{i}{(n+1) \choose i}z((n+1)-i+m)\\&=\sum _{i=0}^{(n+1)}(-1)^{i}{(n+1) \choose i}z((n+1)-i+m)\end{aligned}}\,}

${\displaystyle \sum _{k=0}^{n}(-1)^{k}{n \choose k}(n-k)^{n}=n!\,}$

${\displaystyle n\geq 0}$

${\displaystyle n\geq a\geq 0}$

${\displaystyle \sum _{k=0}^{n}{n \choose k}x^{k}(n-k)^{a}={\frac {n!}{(n-a)!}}(1+x)^{n-a}}$

${\displaystyle a=0\,}$

${\displaystyle \sum _{k=0}^{n}{n \choose k}x^{k}(n-k)^{0}={\frac {n!}{(n-0)!}}(1+x)^{n-0}}$

${\displaystyle \sum _{k=0}^{n}{n \choose k}x^{k}=(1+x)^{n}}$

${\displaystyle a+1\leq n\,}$

${\displaystyle {\frac {\partial }{\partial x}}\sum _{k=0}^{n}{n \choose k}x^{k}(n-k)^{a}={\frac {\partial }{\partial x}}{\frac {n!}{(n-a)!}}(1+x)^{n-a}}$

${\displaystyle \lim _{\Delta x\rightarrow 0}{\cfrac {\sum _{k=0}^{n}{n \choose k}(x+\Delta x)^{k}(n-k)^{a}-\sum _{k=0}^{n}{n \choose k}x^{k}(n-k)^{a}}{\Delta x}}\!\,}$

${\displaystyle =\sum _{k=0}^{n}{n \choose k}(n-k)^{a}\lim _{\Delta x\rightarrow 0}{\cfrac {(x+\Delta x)^{k}-x^{k}}{\Delta x}}\!\,}$

${\displaystyle =\sum _{k=0}^{n}{n \choose k}(n-k)^{a}\lim _{\Delta x\rightarrow 0}{\cfrac {\sum _{j=0}^{k}{k \choose j}x^{j}\Delta x^{k-j}-\sum _{j=0}^{k}{k \choose j}x^{j}}{\Delta x}}\!\,}$

${\displaystyle =\sum _{k=0}^{n}{n \choose k}(n-k)^{a}\lim _{\Delta x\rightarrow 0}{\cfrac {\sum _{j=0}^{k-1}{k \choose j}x^{j}\Delta x^{k-j}}{\Delta x}}\!\,}$